METALLURGICALS: STRESS, LIFE HABITS AND PERSONAL FEELINGS. PREVALENCE AMONG EMPLOYEES - Trotta, Juliano de; Kowalski, Sérgio Candido; Soboll, Lis A. P.; Neto, Plínio Cézar; Rennó, Sarah Larisse M. (Revista Valore, 2022)
Objective: This study aims to verify the incidence of stress and how much it relates to individual characteristics, life habits and personal feelings of metallurgists of a multinational company in the region of Curitiba. Methodology: It is a cross-sectional, descriptive, quantitative study. A survey was conducted using the questionnaire “Perceived Stress Scale” (PSS) and sociodemographic questionnaire with metallurgical employees in 2015. The data were analyzed using descriptive statistics, Fisher’s exact test and Pearson’s Chi-square. Results: Of the 2,200 employees of the company, 1952 (88.7%) were able to participate in the study, 636 of whom (32.58%) were in a situation of stress. There was a prevalence of stress in female individuals, people with sedentary behaviors, smokers, indebted, in those who expressed dissatisfaction with the salary, with the profession and with negative feelings regarding their lives. Thus, the variables that showed a statistically significant relationship with stress (p <0.05) were: sex, physical activity, smoking, satisfaction with salary, work and private life. Conclusion: The study showed an incidence of stress in the metallurgists below the statistics of the working population in general and there was a statistically significant relationship between stress in most of the studied variables regarding life habits and personal feelings.